AKUNTABILITAS DAN TRANSPARANSI BERBASIS BAGI HASIL (ANALISIS TERHADAP KARYAWAN TOKO DI KOTA BEUREUNUEN) - Nasirwan, Mahle Muhammad Ridwan (JURNAL EKONOMI DAN BISNIS ISLAM, 2017)
Research  on  Accountability  and  Transparency  Based  on  the  results  of  this study aims to determine the implementation of Accountability and Transpar- ency Based Revenue in Beureunuen City Store. Some Stores in Beureunuen City implement a profit-sharing system with employees. The study was conducted from March 2016 to February 2017. This research uses qualitative approach. For Collection - to get information about employeesvalidation techniques done by digging information from some informants directly related to the Business. In addition, researchers also con- ducted direct observation at the location of the study to verify the data wheth- er the data obtained from the informant in line with the reality of the field or not. The result of the research analysis shows that the application of Account- ability and Transparency Based on Profit is good. However, there is a weakness in terms of the absence of annual balance sheet. For that researchers offer Bal- ance Sheet report. The implementation of Profit-Based Accountability and Transparency is already well categorized in terms of responsibility to the trustee, providing information to employees and granting the employee rights in accordance with the earn- ings of the company?s profit within one year of Hijriah.